2023
DOI: 10.3390/nano13243113
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Topological Structure Design of Porous Ti–6Al–4V Alloy with Low Modulus and Magnetic Susceptibility

Qian Li,
Qiang Li,
Shasha Lu
et al.

Abstract: Ti–6Al–4V alloy is widely used as a biomaterial for hard tissue replacement, but its Young’s modulus is still higher than that of human bone tissue, which may cause a “stress shielding” effect and lead to implant loosening. In addition, metal implants with low magnetic susceptibility are beneficial for obtaining minimal artifacts in magnetic resonance imaging. To reduce Young’s modulus and magnetic susceptibility of Ti–6Al–4V alloy, a series of irregular prismatic porous structure models were designed based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Additionally, in the compression experiment, the square structure collapsed layer by layer starting from the top surface. The compression experiment conducted on the irregular prismatic porous Ti6Al4V scaffold, as designed by Li et al [5], revealed that an increase in porosity led to a decrease in the compression modulus. Excessive aperture size and unsuitable pore structure can lead to a reduction in the compressive strength of the scaffold, making it more susceptible to damage.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in the compression experiment, the square structure collapsed layer by layer starting from the top surface. The compression experiment conducted on the irregular prismatic porous Ti6Al4V scaffold, as designed by Li et al [5], revealed that an increase in porosity led to a decrease in the compression modulus. Excessive aperture size and unsuitable pore structure can lead to a reduction in the compressive strength of the scaffold, making it more susceptible to damage.…”
Section: Introductionmentioning
confidence: 99%
“…As is well known, osteogenic capacity is the primary function of implanted biomaterials for treating bone defects [ 6 , [16] , [17] , [18] ]. Nowadays, various kinds of artificial biomaterials including metals, ceramics and synthetical polymers have been developed for bone implantation [ 6 , 19 ].…”
Section: Introductionmentioning
confidence: 99%